Step 1:
Rule for translation of a function to the left.
If a function of f(x) = x is translated to the left by a units, the function becomes f(x) = x + a
Rule for reflection across x-axis
The rule for a reflection over the x -axis is (x,y)→(x,−y)
Step 2:
![\begin{gathered} g(x)\text{ = }\sqrt[]{x} \\ \text{When translated 3 units to the left, the function becomes} \\ g(x)\text{ = }\sqrt[]{x\text{ + 3}} \\ \text{when reflected over x-axis} \\ g(x)\text{ = -}\sqrt[]{\text{x + 3}} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/nxpnv1fjjxxmfazt5q9l4amauezswwko39.png)
Final answer
![f(x)\text{ = -}\sqrt[]{x\text{ + 3}}](https://img.qammunity.org/2023/formulas/mathematics/college/nazz6fuic6wbc128z7sp2t935iqpq6t94b.png)